Formulation and Evaluation of Hard Candy Preparation as an Innovative Internal Wound Medicine from Snakehead Fish (Channa striata) Albumin Extract - Diana, Ilvid; Ardelia, Elfi Abidah; Nadriani, Nazilatun; Azizah, Dilna; Widhyati, Dea Nova; Usman, Mohammad Rofik (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Snakehead fish (Channa striata) is another alternative source of albumin protein because it is known to contain important compounds for the human body including high protein, fat, water, and the mineral zinc (Zn). The albumin content in Snakehead fish is an important protein needed by the body and is useful for wound healing. This study aims to make preparations by modifying Snakehead fish albumin into hard candy while maintaining the albumin content. Thus, a more effective way to be consumed in accelerating wound healing was found. The treatment used is Snakehead fish albumin extract with concentrations including F1 (5%), F2 (10%), and F3 (15%). Tests were conducted physically (organoleptic test) and chemically (moisture content test, ash content test, and wound growth activity test). Formulation and evaluation of hard candy preparations of Snakehead fish albumin extract (Channa striata) can be declared successful, as evidenced by the formation of 5 successful formulations into hard candy preparations as evidenced by the results of organoleptic tests, water content tests and ash content tests that have met the standards.